1997
DOI: 10.1111/j.1399-302x.1997.tb00384.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined inhibitory effect of fluoride and hypothiocyanite on the viability and glucose metabolism of Streptococcus mutans, se retype c

Abstract: The separate and combined effects of peroxidase-generated hypothiocyanite (HOSCN/OSCN-) and F- ions on glucose uptake and growth of Streptococcus mutans ATCC 25175 were investigated. S. mutans cells were grown to late exponential or stationary growth phase, harvested, washed and suspended in 2.0 ml of sterilized human whole saliva supplemented with 10 mM D-glucose. This saliva-bacteria mixture was supplemented with 5-150 microM H2O2 at pH 5.0 or 6.5. At pH 5.0, up to 103 +/- 21 microM HOSCN/OSCN- was generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Thus, by measuring the light emission only, the actual killing of bacteria cannot be determined; rather, the "well-being" of a cell is determined. Greger et al (6) found that incubation of S. mutans cells in buffer (pH 5.0) with 1 mM sodium fluoride causes a rapid decrease in the cellular ATP content but does not affect the viability for 4 h. We have previously shown that in saliva at pH 5.0 such NaF concentrations reduce the viability of S. mutans during 20 h of incubation (20). We have also measured the light emission of NaF-salivabacteria suspensions and found that the bioluminescence has already decreased after 10 min of incubation, while the viability is not affected during the first hours (unpublished data).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Thus, by measuring the light emission only, the actual killing of bacteria cannot be determined; rather, the "well-being" of a cell is determined. Greger et al (6) found that incubation of S. mutans cells in buffer (pH 5.0) with 1 mM sodium fluoride causes a rapid decrease in the cellular ATP content but does not affect the viability for 4 h. We have previously shown that in saliva at pH 5.0 such NaF concentrations reduce the viability of S. mutans during 20 h of incubation (20). We have also measured the light emission of NaF-salivabacteria suspensions and found that the bioluminescence has already decreased after 10 min of incubation, while the viability is not affected during the first hours (unpublished data).…”
Section: Discussionmentioning
confidence: 78%
“…Due to the role of this microorganism in the formation of caries lesions, there is constant interest in the antistreptococcal effects of a wide variety of substances, such as antibiotics and oral hygiene products. In our laboratory the susceptibility of S. mutans to innate salivary antimicrobial proteins (lysozyme, lactoferrin, and the peroxidase system of proteins) and the combined effects of these innate factors with immunoglobulin A (IgA) or other antibacterial agents such as fluoride have been studied (19,20,22,25,28). All such studies generally require methods like plate dilution, which is laborious and time-consuming, especially with mutans group streptococci, for which growth on agar plates normally takes several days.…”
mentioning
confidence: 99%
“…Because the pH values in infected sites are generally in the acid range, signi¢cant inhibitory e¡ects of £uoride on defense peroxidases should occur commonly. Recently Lenander-Lumikari et al [67] showed that hypothiocyanite and £uoride could act additively to inhibit growth and glycolysis of S. mutans at pH 5.0 but not at 6.5. Thus, it appears that under some conditions, £uoride may not be antagonistic to peroxide-based defense systems.…”
Section: Inhibition Of Enzymes Involved In Oxidative Stress Andmentioning
confidence: 99%
“…Thus, future products may not only comprise innate host proteins but also specific antibodies against oral pathogens. It should also be stressed that fluoride ions and the peroxidase systems act in an additive manner (Lenander‐Lumikari et al , 1997). To summarize, future products obviously comprise an array of various host‐related antimicrobials at the expense of synthetic agents, such as chlorhexidine and hexetidine.…”
Section: Future Aspectsmentioning
confidence: 99%